Growing older with post‐traumatic stress disorder. Issue 3 (April 2016) - Curran, B.; Collier, E.
Accessible summary: What is known on the subject?: The needs of older people with long‐term mental illness are not very well addressed in policy and research. Older people are not a homogenous group and people ageing with long‐term mental illness have potentially unique or specific needs. What this paper adds to existing knowledge?: A unique example of the idiosyncratic and contextual nature of individual strengths and the abilities in managing personal recovery when experiencing long‐term mental illness. Emotional exhaustion experienced after long‐term mental health compromises the ability to manage feelings, potentially a special feature of life time mental ill health. What are the implications for practice?: Recognition that the hard work involved in successfully managing long‐term personal recovery may be important in preventing suicide in later life. The need to understand a person's life story to make sense of their experience of mental illness and to recognize long‐term mental illness to later life as part of a persons' established identity. The importance of appreciating the place of early memories for understanding older person's mental health in their present. Abstract: Introduction: Ageing with mental illness is a neglected area of research and policy. People who grow older to later life with ongoing mental health problems may not have their needs well understood. This understanding is important if mental health services are to ensure direct or indirect age discrimination is avoided. Aim: This paper aims to explore issues relating to later life and ageing with mental illness focused on the story of Bernard (who was 84 years of age at the time of writing) who lived with a diagnosis of post‐traumatic stress disorder (PTSD). Method: The paper is co‐authored by Bernard and the researcher he originally told his story to as a participant in a biographical research study exploring mental ill health through the life course. In the original research study, Bernard completed a curriculum vitae (CV) of his life which informed two personalised interviews. An edited version of this is presented in this paper. Implications for practice are discussed in the context of life course, recovery, self‐help and preventing suicide. The narrative illustrates how time, memory and meaning interweave and how ageing with mental illness become part of a person's ongoing identity.